2012
DOI: 10.32502/sm.v2i2.1439
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko yang Berhubungan dengan Kejadian Tuberkulosis di RSK Paru Palembang Periode Januari-Desember 2010

Abstract: Indonesia menempati peringkat negara dengan beban Tuberkulosis (TB) ke-5 tertinggi di dunia denganperkiraan 61.000 kematian akibat TB setiap tahun. Penelitian ini bertujuan untuk mengetahuihubungan faktor risiko terhadap kejadian tuberkulosis. Sampel dalam catatan medis dari Rumah SakitParu Palembang sejak 1 Januari dan 31 Desember 2010 sebanyak 163 sampel yang diambilmenggunakan sampling sistematis edaran. Desain penelitian Cross Sectional dan uji Chi Squaremelihat hubungan antar variabel, dengan tingkat kepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The dependent variables in this study were age, education, gender, and contact history, while the independent variable was pulmonary tuberculosis. The results of this study are in line with the findings of [5] and [6], It concluded that individuals aged 15-55 were 1.5 times more likely to suffer from pulmonary TB than those aged 15 or >55, but that there was no correlation between age and the prevalence of TB in this age group.…”
Section: Methodssupporting
confidence: 91%
“…The dependent variables in this study were age, education, gender, and contact history, while the independent variable was pulmonary tuberculosis. The results of this study are in line with the findings of [5] and [6], It concluded that individuals aged 15-55 were 1.5 times more likely to suffer from pulmonary TB than those aged 15 or >55, but that there was no correlation between age and the prevalence of TB in this age group.…”
Section: Methodssupporting
confidence: 91%
“…In almost all developing countries, smoking prevalence is more than 50% in men compared to women. 17 People who smoke can lower the body's immunity to be more susceptible to TB. 18 The majority of respondents have normal nutrition, followed by underweight, then obesity, after that several underweight and overweight have the same value.…”
Section: Child Characteristicmentioning
confidence: 99%